Biology-guided radiotherapy in metastatic prostate cancer: time to push the envelope? - Lancia, Andrea; Ingrosso, Gianluca; Detti, Beatrice; Festa, Eleonora; Bonzano, Elisabetta; Linguanti, Flavia; Camilli, Federico; Bertini, Niccolò; La Mattina, Salvatore; Orsatti, Carolina; Francolini, Giulio; Abenavoli, Elisabetta Maria; et al. (Frontiers in Oncology, 2024)
The therapeutic landscape of metastatic prostate cancer has undergone a profound revolution in recent years. In addition to the introduction of novel molecules in the clinics, the field has witnessed a tremendous development of functional imaging modalities adding new biological insights which can ultimately inform tailored treatment strategies, including local therapies. The evolution and rise of Stereotactic Body Radiotherapy (SBRT) have been particularly notable in patients with oligometastatic disease, where it has been demonstrated to be a safe and effective treatment strategy yielding favorable results in terms of disease control and improved oncological outcomes. The possibility of debulking all sites of disease, matched with the ambition of potentially extending this treatment paradigm to polymetastatic patients in the not-too-distant future, makes Biology-guided Radiotherapy (BgRT) an attractive paradigm which can be used in conjunction with systemic therapy in the management of patients with metastatic prostate cancer.